The Effectiveness of Telenursing on The Patient’s Quality of Life: A Review - Yusshy Kurnia Herliani; Alisya Putri Shabrina; Nadia Putri Andrini; Ananda Fairuz Melawardani; Hani Aisya Rahmi; Muhammad Rifki Maulana (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
COVID-19 is a pandemic case that has occurred throughout the world, resulting in restrictions on human activity in all areas, including health services, so that telenursing is one of the long-distance health service solutions in providing interventions. Improved quality of life is an indicator of successful intervention in patients. The study aimed to identify the effectiveness of telenursing in patients' quality of life. This study was conducted using a literature review method with the keywords